Folate receptor-directed orthogonal click-functionalization of siRNA lipopolyplexes for tumor cell killing in vivo. (September 2018) - Klein, Philipp Michael; Kern, Sarah; Lee, Dian-Jang; Schmaus, Johannes; Höhn, Miriam; Gorges, Jan; Kazmaier, Uli; Wagner, Ernst
Abstract: The delivery of small interfering RNA (siRNA) and its therapeutic usage as an anti-cancer agent requires a carrier system for selective internalization into the cytosol of tumor cells. We prepared folate-bearing formulations by first complexing siRNA with the novel azido-functionalized sequence-defined cationizable lipo-oligomer 1106 (containing two cholanic acids attached to an oligoaminoamide backbone in T-shape configuration) into spherical, ∼100–200 nm sized lipopolyplexes, followed by surface-functionalization with various folate-conjugated DBCO-PEG agents. Both the lipo-oligomer and the different defined shielding and targeting agents with mono- and bis-DBCO and varying PEG length were generated by solid phase supported synthesis. A bivalent DBCO surface agent with a PEG24 spacer was identified as the optimal formulation in terms of nanoparticle size, folate receptor (FR) targeting, cellular uptake and gene silencing in vitro . Notably, near-infrared fluorescence bioimaging studies showed that double-click incorporation of bivalent DBCO-PEG24 resulted in siRNA/ 1106 / DBCO 2 -ss 2 -PEG 24 -FolA lipopolyplexes with extended biodistribution and intratumoral delivery in a subcutaneous FR-positive leukemia mouse model. Intravenous administration of analogous therapeutic siRNA lipopolyplexes (directed against the kinesin spindle motor protein EG5) mediated tumoral EG5 mRNA knockdown by ∼60% and, in combination with the novel antitubulin drug pretubulysin, significantly prolonged survival of aggressive leukemia bearing mice without noticeable side effects. Graphical abstract: